A review of the genera Amauta Houlbert, 1918 and Divana J.Y. Miller, 1982 (Lepidoptera: Castniidae) with description of a new genus - Worthy, Robert; González, Jorge M.; Zilli, Alberto (Zootaxa, 2022)
The genera Amauta Houlbert, 1918 and Divana J.Y. Miller, 1982 are revised, with discussion of diagnostic features of males and females of all taxa. Details on their nomenclatural history, biogeography, and biology are included to solve several nomenclatural issues. Lectotypes are designated for Castnia (Amauta) papilionaris affinis Rothschild, 1919 and Castnia tricolor C. Felder & R. Felder, 1874. The status of the following taxa is revised: Amauta procera (Boisduval, [1875]) stat. rest., Amauta angusta (H. Druce, 1907) stat. rest., Castnia ambatensis Houlbert, 1917 syn. nov. of Castnia papilionaris papilionaris Walker, [1865], Castnia velutina Houlbert, 1917 syn. nov. of Castnia papilionaris papilionaris Walker, [1865], and Castnia diva chiriquiensis Strand, 1913 syn. nov. of Castnia diva diva Butler, 1870. Other taxa are revised, and their taxonomic status clarified. A new genus Vadina gen. nov. is proposed for Castnia hodeei Oberthür, 1881, which is removed (comb. nov.) from Telchin Hübner, [1825], whilst Amauta stat. rest. and Divana stat. rest., subsumed into Telchin in the most recent revision of the family, are herein reinstated as valid genera.